Prehospital Atrial Fibrillation: Clinical and Economic Aspects - V. T. Dolgikh; V. G. Epifanov (Общая реаниматология)
Objective: to retrospectively study the results of emergency medical care for patients with uncomplicated attacks of atrial fibrillation and to provide a clinical and economic assessment of their prehospital management tactics. Material and methods. A comparative retrospective study was conducted to examine the results of emergency medical care rendered to 1200 patients with uncomplicated atrial fibrillation attacks lasting as long as 24 hours. Ambulance call and outpatient cards and inpatient case reports were used. A clinical and economic assessment of the prehospital management tactics for the patients was made. Results. The prehospital therapy of atrial fibrillation was found to be ineffective in the first hour of observation. In more than 90% of cases, an atrial fibrillation attack was eliminated by the end of the first 24 hours regardless of which antiarrhythmic agent had been used. Conclusion. The proposed prehos-pital management tactics for patients with uncomplicated atrial fibrillation attacks lasting as long as 24 hours make it possible to decrease the length of stay of a called ambulance team and to enhance its efficiency, without reducing the clinical effect of performed antiarrhythmic therapy. Key words: atrial fibrillation, emergency medical care, prehospi-tal stage, clinical and economic analysis.